(untitled) (Raparin Journal of Humanities (RJH), 2024)
The study aims to design tests to measure some physical abilities in the study sample, to find standard grades and levels for some tests of physical abilities in the study sample, preparing equations to predict the level of performance skill of soccer players in terms of mobility tests in the research sample. The researcher used the descriptive approach, and the research community was selected from football academy players with ages (13-14) years in Raparin. The research sample was selected intentionally, which included (260) players. So as to reach the results, the researcher used a set of statistical programs by using SPSS. It was concluded to find and determine the grades and standard levels modified for the research sample in the physical tests. It is concluded that these tests can be accepted as an evaluation method and indicator to show the player’s physical and skillful condition, and to define an equation to predict the level of performance skill in terms of physical abilities.